Aggregation dynamics of molecular bonds between compliant materials. Issue 14 (23rd February 2015) - Jiang, Hongyuan; Qian, Jin; Lin, Yuan; Ni, Yong; He, Linghui
Abstract : In this paper, we develop a mechanochemical modeling framework in which the spatial-temporal evolution of receptor–ligand bonds takes place at the interface between two compliant media in the presence of an externally applied tensile load. Abstract : In this paper, we develop a mechanochemical modeling framework in which the spatial-temporal evolution of receptor–ligand bonds takes place at the interface between two compliant media in the presence of an externally applied tensile load. Bond translocation, dissociation and association occur simultaneously, resulting in dynamic aggregation of molecular bonds that is regulated by mechanical factors such as material compliance and applied stress. The results show that bond aggregation is energetically favorable in the out-of-equilibrium process with convoluted time scales from bond diffusion and reaction. Material stiffness is predicted to contribute to adhesion growth and an optimal level of applied stress leads to the maximized size of bond clusters for integrin-based adhesion, consistent with related experimental observations on focal adhesions of cell–matrix interactions. The stress distribution within bond clusters is generally non-uniform and governed by the stress concentration index.